The Effects of Consumers’ Buying Behavior on the E-commerce in Highly Developed Emerging Market and Developed Market: The Case of Singapore and Austria - Jia Yun Moerth-Teo; Vito Bobek; Tatjana Horvat (Naše gospodarstvo/Our economy, 2021)
The e-commerce is becoming increasingly essential and principally relevant in the modern world, especially in the current pandemic. Due to the increased use of the Internet, the growth of e-commerce has escalated. This research focuses on the e-commerce environments of Singaporean and Austrian markets. It contains an outline touching on the theoretical parts and the conduct of an empirical study where the survey results from 206 participants were studied, analysed, and compared. The statistical methods chosen for this research were the t-test analysis and the correlation analysis. The empirical study served as a quantitative discussion on both countries' e-commerce markets. The analysis of the completed questionnaires provided a better and clear understanding of the buying behaviours and their potential impact on the e-commerce markets in Singapore and Austria. Considering the results from the comparisons, the research has also highlighted some interesting findings and differences in the buying behaviours of Singaporean and Austrian shoppers.